Reformasi Kultural Orde Baru dalam Perspektif Postmodernisme - Arinto Nurcahyono (Universitas Islam Indonesia, 1999)
As a discourse of Postmodernism, deconstruction has a great importance to be used as a tool of cultural reform in Indonesia. When The New Era was in power it developed the